(untitled) (Current Horticulture, 2024)
Bitter gourd (Momordica charantia L.) is important vegetable crop. It is a cross-pollinated crop and can be grown in both kharif and rabi seasons. Micronutrients such as iron, zinc, boron, manganese etc. play a vital role in modifying its growth and development. The deficiency of micronutrients adversely affects the production of vegetable besides quality. Therefore, an experiment was conducted on foliar feeding of micronutrients to evaluate its effect on growth parameters and fruit yield of bitter gourd.